Pulp response after application of two resin modified glass ionomer cements (RMGICs) in deep cavities of prepared human teeth - Souza Costa, Carlos A. de [UNESP]; Ribeiro, Ana Paula D. [UNESP]; Aparecida Giro, Elisa M. [UNESP]; Randall, Ros C.; Hebling, Josimeri [UNESP] (Elsevier B.V., 2011)
Objectives: This study evaluated the human pulp response to the application of two RMGICs in deep cavities in vivo. Methods: The cavity floor prepared on the buccal surface of 34 premolars was lined with VBP (VBP), Vitrebond (VB) or Dycal (R) (DY), and restored with composite resin. Additional teeth were used as an intact control group. After 7 or 30-60 days, the teeth were extracted and processed for histological evaluation. The following histological events were scored: inflammatory response, tissue disorganization, reactionary dentin formation and presence of bacteria. Results: At 7 days, VBP and VB elicited a mild inflammatory pulpal response in about 70% of specimens and in 1 specimen for DY. Only 1 specimen of each RMG-ICs exhibited moderate tissue disorganization. Bacteria and reactionary dentin formation were not found. At 30-60 days, about 20% of specimens lined with RMGICs showed a persistent mild inflammatory pulp response while no inflammatory reaction was observed for DY. Moderate tissue disorganization occurred with both materials. Bacteria were found only in 1 VBP specimen. The mean remaining dentin thickness (RDT) in specimens lined with VBP, VB or DY ranged from 342.3 to 436.1 mu m, and no statistically significant differences in RDT were found among materials or periods (two-way ANOVA, p > 0.05). Comparison of the two RMGICs tested for the histological events at each period showed statistically similar results (Kruskal-Wallis, p > 0.05). Significance: The use of the new Vitrebond formulation (VBP) in deep cavities in vivo caused mild initial pulp damage, which decreased with time, indicating acceptable biocompatibility. (C) 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Dental materials; Biocompatibility; Glass ionomer cements; Pulp